2017
DOI: 10.18203/2394-6040.ijcmph20175342
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption among college students in Minahasa, Indonesia: a cross-sectional study towards the formulation of intervention strategies

Abstract: Background: College students are within the high-risk group to experience the full spectrum of alcohol-related psychopathologies, ranging from initial contact with alcohol to the severe problematic drinking. The prevalence, degree of severity, reasons of drinking, among other variables, however, have been inconsistent across studies. Therefore, it is crucial to replicate such studies in different socio-cultural settings to synthesize a broader understanding about alcohol-consuming behavior and formulating inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…Moreover, alcohol was found to be the substance that was most abused by university students in the United Kingdom and Ireland [16]. However, the reported prevalence of alcohol consumption is lower in our study than in those conducted in Asia [17][18][19], Europe [20][21][22] and African region [23,24]. This may be attributable to geographical differences in beliefs, religious and cultural practices, environmental factors, the accessibility and availability of alcohol, urbanization, lifestyle, national laws, and governmental and legal enforcement of alcohol-related regulations [1].…”
Section: Discussioncontrasting
confidence: 55%
“…Moreover, alcohol was found to be the substance that was most abused by university students in the United Kingdom and Ireland [16]. However, the reported prevalence of alcohol consumption is lower in our study than in those conducted in Asia [17][18][19], Europe [20][21][22] and African region [23,24]. This may be attributable to geographical differences in beliefs, religious and cultural practices, environmental factors, the accessibility and availability of alcohol, urbanization, lifestyle, national laws, and governmental and legal enforcement of alcohol-related regulations [1].…”
Section: Discussioncontrasting
confidence: 55%
“…A survey in 2012 showed that more Indonesian male adolescents (39.2%) than female adolescents (5.9%) drank alcohol [5]. In some areas of Indonesia, drinking alcohol has become part of the culture as a form of celebration on certain occasions even though consuming alcohol is prohibited by religion [6]. Furthermore, people who try alcohol tend to initiate other risky behaviors such as drug abuse.…”
Section: Introductionmentioning
confidence: 99%